The Intuitive Thinking Ability of Students of Grade XI Science at SMA Negeri 4 Palu through the Implementation of Discovery Learning Model on Colloidal Material - Muh. F. I. Ote; Paulus H. Abram; Purnama Ningsih (Jurnal Akademika Kimia, 2020)
This study aimed to describe the intuitive thinking ability in Grade XI SMA Negeri 4 Palu through the implementation of discovery learning model on Colloidal material. This study was a One-Shot Case Study design. The population of this study was all students of grade XI Science at SMA Negeri 4 Palu, and the sample was Class XI Science 3 as the replication class 1 and class XI Science 6 as the replication class 2. The results obtain the intuitive thinking ability of replication class 1 is that the students who solved the problem with a reasonable answer, that is 86.43% in the very high category. Students who solved problems using prior knowledge and experience, that is equal to 77.14% in the high category, and students who solved problems based on generalization of examples or concepts, that is 84.46% in the very high category. While the intuitive thinking ability of replication class 2 is that the students who solved problems with a reasonable answer is 52.85%, in the medium category. Students who solved problems using prior knowledge and experience, that is equal to 76.42% included in the high category, and students who solved problems based on generalization of examples or concepts that is equal to 83.92% in the very high category.